Teaching Holocaust memory in a translation classroom: two didactic and research-teaching integration proposals in higher education0. - Fernández-Gil, María Jesús; Bascoy Lamelas, Montserrat (Pulso. Revista de educación, 2023)
Insofar as it is a common negative reference point and the source of departure for European identity (Judt, 2006, p.1146), the historical event of the Holocaust has become a central part for the field of education, in general, and for higher education institutions, in particular. This paper highlights the importance of Holocaust memory as a tool for innovation in teaching in a translation classroom. To that intent and purpose, we present two didactic proposals implemented in the Grado en Lenguas Modernas y Traducción at the Universidad de Alcalá. These educational actions are aimed at enhancing translation competence, which is the main objective of the courses within which the proposals were developed, while evoking at the same time commitment and solidarity with the Other and fortifying society against hate speech; they develop thereby social and civic competences. In addition, these experiences are a good example of effective integration of research and teaching. Creating a link between research and teaching is fundamental, as these are the two core functions of universities, and one of the arenas where knowledge is created.
Keywords: Holocaust; Europe; Memory; The Other; Translation Competence; Education